The legal geographies of transnational cyber-prosecutions: extradition, human rights and forum shifting. - Mann, Monique; Warren, Ian; Kennedy, Sally (Global Crime, 2018)
This article describes legal and human rights issues in three cases of transnational online offending involving extradition requests by the United States (US). These cases were selected as all suspects claimed the negative impacts of autism spectrum disorders (ASDs) were sufficient to deny extradition on human rights grounds. We demonstrate how recent developments in UK and Irish extradition law raise human rights and prosecutorial challenges specific to online offending that are not met by established protections under domestic and internationally sanctioned approaches to extradition or human rights law. In these cases, although the allegedly unlawful conduct occurred exclusively online and concurrent jurisdiction enables prosecution at both the source and location of harm, we demonstrate why national courts hearing extradition challenges are extremely reluctant to shift the trial forum. We conclude by discussing the implications of the new geographies of online offending for future criminological research and transnational criminal justice.